Wild bonobo and chimpanzee females exhibit broadly similar patterns of behavioral maturation but some evidence for divergence. Issue 1 (6th October 2019) - Lee, Sean M.; Murray, Carson M.; Lonsdorf, Elizabeth V.; Fruth, Barbara; Stanton, Margaret A.; Nichols, Jennifer; Hohmann, Gottfried
Abstract: Objectives: Primates exhibit variation in rates of growth and development. Variation in female growth and development across ape species appears to be explained by the Ecological Risk Aversion Hypothesis (ERAH). Indeed, existing data on variation in somatic growth and reproductive maturation between humans' closest living ape relatives, bonobos and chimpanzees, appear to be consistent with this hypothesis. However, existing data on behavioral maturation between the two species appear to contradict this hypothesis. We present novel behavioral data on infant and juvenile females from wild populations of both species in order to further evaluate predictions of the ERAH as it relates to the speed of behavioral maturation. Materials and methods: We analyzed 3 years of behavioral data on 17 female bonobos (<8 years of age) from LuiKotale, Democratic Republic of the Congo and 40 years of behavioral data on 30 age‐matched female chimpanzees from Gombe, Tanzania. We compared the timing of (a) the attainment of independence from mothers and (b) the development of social skills using the following proxies: proximity between females and their mothers and the time that females spent engaged in eating, suckling, social play, social grooming, and riding on their mothers. Results: We did not find species differences in the proportion of time that females spent in contact with their mothers or engaged in eating, suckling, social play, or social grooming. Female bonobos spent more time riding on their mothers than did female chimpanzees. Female bonobos spent more time at distances greater than 5 m from their mothers during the ages of 3–8 years, but females did not differ during the ages of 0–3 years. Discussion: Behavioral maturation is largely similar between females of the two species based on the ages and proxies considered herein. We propose alternative explanations for the differences that we found in proximity and riding that do not invoke differences in underlying rates of maturation.